2006
DOI: 10.1038/sj.ejcn.1602497
|View full text |Cite|
|
Sign up to set email alerts
|

Folate intakes and folate biomarker profiles of pregnant Japanese women in the first trimester

Abstract: Objective: To assess the status of dietary folate intake, serum and red blood cell (RBC) folate, and related nutritional biomarkers in healthy Japanese women in early pregnancy. Design: A cross-sectional, observational study. Subjects: Pregnant women in the first trimester, at 7-15 weeks gestation (n ¼ 70), who were not consuming any folate supplements or folate fortified foods. Methods: Three-day dietary records were obtained from each subject to assess dietary folate intake. Blood samples were collected for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 28 publications
2
25
0
3
Order By: Relevance
“…Of the remaining 95 papers, 63 were excluded on the basis of the full text. The remaining 32 articles are included in this review, as shown in Supplemental S1 (Adaikalakoteswari et al, ; Ambroszkiewicz, Chelchowska, Lewandowski, Gajewska, & Laskowska‐Klita, ; Baker et al, ; Bakker et al, ; Bergen et al, ; Bodnar et al, ; Coker et al, ; Dayaldasani et al, ; Frery et al, ; D. Furness et al, ; D. L. Furness, Yasin, Dekker, Thompson, & Roberts, ; Gadowsky et al, ; Hay et al, ; Jauniaux, Johns, Gulbis, Spasic‐Boskovic, & Burton, ; Knight et al, ; Knudtson et al, ; Larroque et al, ; Matsuzaki et al, ; McDonald, Perkins, Jodouin, & Walker, ; Mito et al, ; Nilsen et al, ; Ozerol, Ozerol, Gokdeniz, Temel, & Akyol, ; Pagan, Hou, Goldenberg, Cliver, & Tamura, ; Prasodjo et al, ; Relton et al, ; Sram, Binkova, Lnenickova, Solansky, & Dejmek, ; Stark et al, ; Stark, Pawlosky, Sokol, Hannigan, & Salem Jr., ; Van Uitert et al, ; van Wersch, Janssens, & Zandvoort, ; Vandevijvere, Amsalkhir, Van Oyen, & Moreno‐Reyes, ; Yila et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining 95 papers, 63 were excluded on the basis of the full text. The remaining 32 articles are included in this review, as shown in Supplemental S1 (Adaikalakoteswari et al, ; Ambroszkiewicz, Chelchowska, Lewandowski, Gajewska, & Laskowska‐Klita, ; Baker et al, ; Bakker et al, ; Bergen et al, ; Bodnar et al, ; Coker et al, ; Dayaldasani et al, ; Frery et al, ; D. Furness et al, ; D. L. Furness, Yasin, Dekker, Thompson, & Roberts, ; Gadowsky et al, ; Hay et al, ; Jauniaux, Johns, Gulbis, Spasic‐Boskovic, & Burton, ; Knight et al, ; Knudtson et al, ; Larroque et al, ; Matsuzaki et al, ; McDonald, Perkins, Jodouin, & Walker, ; Mito et al, ; Nilsen et al, ; Ozerol, Ozerol, Gokdeniz, Temel, & Akyol, ; Pagan, Hou, Goldenberg, Cliver, & Tamura, ; Prasodjo et al, ; Relton et al, ; Sram, Binkova, Lnenickova, Solansky, & Dejmek, ; Stark et al, ; Stark, Pawlosky, Sokol, Hannigan, & Salem Jr., ; Van Uitert et al, ; van Wersch, Janssens, & Zandvoort, ; Vandevijvere, Amsalkhir, Van Oyen, & Moreno‐Reyes, ; Yila et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Kimchi and rice are the main sources of folate in Koreans, which contributed about 30~40% of folate intake [24]. Mito et al [28] reported that the mean serum and RBC folate concentrations in Japanese pregnant women who were not consuming folic acid supplements were 10.3 and 519 ng/mL, respectively, which were higher than reported in other countries.…”
Section: Discussionmentioning
confidence: 99%
“…One might have expected the women with higher parity and or educational attainment to have more reproductive health knowledge in this respect. It is also evident that the uptake of any dietary supplements whatever is very low (about 10 %) among this study population, and that their current low consumption levels of possible natural food sources of FA could not be hoped to serve them well in achieving the optimal serum folate levels for preventing the NTDs [20,26,27].…”
Section: Primary Prevention Of Cns Birth Defectsmentioning
confidence: 91%